Anillos anuales de crecimiento en cafetos (Coffea arabica L.) y sus usos potenciales - Gerez Fernández, P; Peters, C.M. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
Annual growth rings are reported for coffee trees growing in the Coatepec region of Veracruz, Mexico. Ring structure and formation are briefly discussed and the potential use of growth rings in coffee are highlighted.